Three new species of Marcepania Jałoszyński (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Three new species of the Oriental genus Marcepania Jałoszyński are described: M. halva sp. n. (Sumatra), M. krowka sp. n. (Sumatra), and M. daifuku sp. n. (Thailand). Previously Marcepania was known from Borneo, Malay Peninsula and Palawan. A female of M. halva was disarticulated to verify its generic placement and its fine structures are illustrated.